Analyzing Effective Learning Models for Developing Problem-Solving Skills in Primary School Students - Rosul Juned (UM Purwokerto Press, 2025)
Given the challenges of the Interconnected era, problem-solving skills play a vital and indispensable role in the development of individuals in academic, professional as well as everyday life.This study investigates effective learning models that foster these skills among elementary students at SD Negeri Kasmaran, Banjarnegara, Indonesia. Employing a qualitative case study design, the research draws from classroom observations, interviews, and documentation to identify the characteristics and impacts of various pedagogical approaches. Findings indicate that student-centered learning models, particularly Project-Based Learning (PjBL), Problem-Based Learning (PBL), Cooperative Learning, and Inquiry-Based Learning, significantly enhance students' problem-solving capabilities. The study further discusses implementation challenges and proposes strategic solutions to optimize learning outcomes.